DSM-IV-TR casebook and treatment guide for child mental health - Galanter, Cathryn A. 1968-.; Jensen, Peter S. 1949-.; IG Publishing (Washington, DC American Psychiatric Pub., 2009)
The book is designed to be both an indispensable reference and a teaching tool for trainees, trainers, and clinicians of child and adolescent psychiatry, including social workers, psychiatrists, psychologists, and nurse clinicians.
pt. 1: Classic cases. Introduction to classic cases / Peter S. Jensen, Cathryn A. Galanter -- Trouble paying attention: attention-deficit / hyperactivity disorder / Stephen P. Hinshaw -- Trouble with transitions: Does my child have autism? / Susan Bacalman, Robert L. Hendren -- Living in her parents' shadow: separation anxiety disorder / Andrea M. Victor, Gail A. Bernstein -- Chatterbox at home: selective mutism / Bruce Black -- Everything bothers her: major depressive disorder / John S. March -- Excessively silly: bipolar disorder / Mary Kay Gill, Boris Birmaher -- Life of the party: chronic marijuana use / Paula Riggs -- My mind is breaking: psychosis / Julia W. Tossell, Judith L. Rapoport -- She just won't eat a thing: anorexia nervosa / E. Blake Finkelson, B. Timothy Walsh -- The blinker: tourette's disorder / Daniel A. Gorman, Bradley S. Peterson -- She never falls asleep: disordered sleep in an adolescent / Ronald E. Dahl, Allison G. Harvey -- The world is a very dirty place: Obsessive-compulsive disorder / Susan E. Swedo -- pt. 2: Comorbid complexity. Introduction to comorbid complexity / Peter S. Jensen, Cathryn A. Galanter -- Stealing the car: disruptive behavior in an adolescent / Peter S. Jensen -- Zero tolerance: threats to harm a teacher in elementary school / Karen C. Wells -- Anxious adolescent in the emergency room: possible abuse of prescription medications / Jeffrey J. Wilson -- The worried child: a child with multiple anxiety disorders / Wendy K. Silverman, Carla E. Marin -- Affective storms: a careful assessment of rage attacks / Gabrielle A. Carlson -- Failing out of school: language and reading weakness / Lynn M. Wegner -- Functional abdominal pain in a child with inflammatory bowel disease / Eva M. Szigethy -- pt. 3: Toughest cases: diagnostic and treatment dilemmas. Introduction to toughest cases / Peter S. Jensen, Cathryn A. Galanter -- Frequent tantrums: oppositional behavior in a young child / Ross W. Greene, J. Stuart Ablon -- Toddler with temper tantrums: a careful assessment of a dysregulated preschool child / Helen Egger -- Won't leave his room: clinical high risk for developing psychosis / Cheryl M. Corcoran -- I just want to die: double depression / David A. Brent -- Cutting helps me feel better: nonsuicidal self-injury / Matthew K. Nock, Tara L. Deliberto -- From foster care to the state hospital: psychotic symptoms in a child who is the victim of neglect / Patricia K. Leebens -- pt. 4: Kids in crisis psychopathology in the context of social stressors. Introduction to kids in crisis / Peter S. Jensen, Cathryn A. Galanter -- Suicidal ideation after supervised visits with biological mom: depressed mood in a child in foster care / Paramjit T. Joshi, Lisa M. Cullins -- The legacy of war: irritability and anger in an adolescent refugee / Brian L. Isakson, Christopher M. Layne -- Moody Child: depressed in context of parental divorce / Sharlene A. Wolchik, Irwin N. Sandler -- It should have been me: childhood bereavement / Cynthia R. Pfeffer -- Won't settle down: disinhibited attachment in a toddler / Stacy S. Drury, Charles H. Zeanah -- pt. 5: Diagnostic and treatment decision making. Diagnostic decision making / Cathryn A. Galanter, Peter S. Jensen -- Research and clinical perspectives on diagnostic and treatment decision making: whence the future?
Electronic reproduction.
Keywords: Child psychiatry -- Case studies; Mentally ill children -- Care; Mentally ill children -- Rehabilitation; Electronic books